Phase field crystal simulation of stress induced localized solid-state amorphization in nanocrystalline materials. (6th November 2017) - Xi, Wen; Song, Xiaoqing; Hu, Shi; Chen, Zheng
Abstract: In this work, the phase field crystal (PFC) method is used to study the localized solid-state amorphization (SSA) and its dynamic transformation process in polycrystalline materials under the uniaxial tensile deformation with different factors. The impacts of these factors, including strain rates, temperatures and grain sizes, are analyzed. Kinetically, the ultra-high strain rate causes the lattice to be seriously distorted and the grain to gradually collapse, so the dislocation density rises remarkably. Therefore, localized SSA occurs. Thermodynamically, as high temperature increases the activation energy, the atoms are active and prefer to leave the original position, which induce atom rearrangement. Furthermore, small grain size increases the percentage of grain boundary and the interface free energy of the system. As a result, Helmholtz free energy increases. The dislocations and Helmholtz free energy act as the seed and driving force for the process of the localized SSA. Also, the critical diffusion-time step and the percentage of amorphous region areas are calculated. Through this work, the PFC method is proved to be an effective means to study localized SSA under uniaxial tensile deformation.